Leaf hydraulic decline coordinates stomatal and photosynthetic limitations through anatomical adjustments under drought stress in cotton - Li, Xiuli; Wang, Shuo; Zhu, Lingxiao; Zhang, Peng; Qi, Hong; Zhang, Ke; Sun, Hongchun; Zhang, Yongjiang; Lei, Xiaopeng; Li, Anchang; Wang, Zhanbiao; Li, Cundong; et al. (Frontiers in Plant Science, 2025)
Drought stress detrimentally impacts leaf water transport, lowering transpiration and photosynthetic efficiency and ultimately reducing seed cotton yield. This study investigated the relationship between leaf hydraulic and photosynthetic traits in cotton under three moisture treatments: control (CK), moderate drought (MD), and severe drought (SD). By day 28 after drought stress, drought stress significantly impaired leaf hydraulics, as demonstrated by decreases in leaf hydraulic conductivity (Kleaf) (9.81% under MD, 12.93% under SD) and leaf water potential (5.79% under MD, 17.54% under SD). Key contributing factors included reduced xylem vessel diameter and number, diminished minor vein density, and decreased aquaporin gene expression. In addition, stomatal width and aperture were significantly reduced with increasing drought severity. Compared with CK, stomatal width and aperture decreased by 6.83% and 13.22% under MD, and by 20.59% and 19.92% under HD. These changes resulted in lower stomatal conductance, net photosynthetic rate, and biomass accumulation, inhibiting growth and reducing plant height, stem diameter, and leaf area. The results of this study provide insights into the anatomical and physiological mechanisms underlying leaf hydraulic conductivity under drought stress.